Assessment of green inhibitor on the crystal structures of carbonated concrete - Abdulrahman, A.; Ismail, Mohamed (Penerbit Universiti Teknologi Malaysia, 2014)
The present paper involves studies of inhibitors on carbonation depth and carboaluminates of concrete which was exposed to accelerated carbonation. Three inhibitors used were; calcium nitrite, ethanolamine and eco-friendly green Bambusa Arundinacea. Concrete mix was designed to be 30 MPa with 0.45 W/C ratios which was chloride contaminated by 1.5% weight of cement content from analytical grade of magnesium chloride salt. Inhibitors additions were 2% and 4% weight of cement content. The results show that Bambusa arundinacea inhibitor distinctively shows lowest level of carbonation. This developed hydrophobic green inhibitor characteristics was able to form impermeable barrier against CO2gas. Additionally, hemicarboaluminate phases appears at hydration in calcite-containing Portland cement, even in the presence of two inhibitors (calcium nitrite and ethanolamine) which gradually converted to monocarboaluminate. Whereas, Bambusa arundinacea inhibitor causes the saturation of portlandite that maintained Ca/Si ratio above 1.65 and C-S-H remain unaffected by carbonation.